Local Knowledge-based Citizenship Learning Model to Increase Ecological Awareness in the Indonesia-Malaysia Border Area - Moad; Hadi Rianto; Muhamad Imaduddin; Nawawi; Syafrial Nur (Jurnal Kewarganegaraan, 2026)
High gap between ecological knowledge and pro-environmental action remains a critical challenge for sustainability, particularly in ecologically sensitive border regions. This study addresses this gap by developing and testing a Civic Ecological Transformation (CET) learning model based on local knowledge to enhance students’ ecological awareness in the Indonesia–Malaysia border region. Using a mixed-methods approach with a sequential exploratory design, the study began with a qualitative exploration (interviews, FGDs, observations) to identify local cultural values, followed by a quantitative phase (one-group pretest-posttest, PLS-SEM) to test the model’s effectiveness. The findings reveal that the integration of local knowledge such as belalek, saprahan, and tepung tawar significantly improves ecological awareness. Path analysis confirms the effect of the CET learning model is fully mediated by this integration of local knowledge. The CET model effectively fosters ecological citizenship and supports the achievement of SDG 4, 13, and 15, contributing a pedagogical innovation for Civic Education rooted in environmental sustainability.